Impact of Psychological Stress on Cortisol Levels and Clinical Characteristics among Breast Cancer Patients - ABBAS, MUHAMMAD UMAR; ABBAS, AIMAN; AMJAD, SOHAIL; REHMAN, VANEEZA; ALI, AKHTAR; ALI, RIMSHA; AHMED, ADEEL (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Cancer Breast cancer has been one of the most prevalent sources of cancer morbidity and mortality in women around the world especially in Pakistan. Psychological stress has been viewed as a major key factor associated to cancer development through neuroendocrine pathways, especially via cortisol dysregulation. Nevertheless, there are few studies on the association between psychological stress and cortisol level in patients with breast cancer in Pakistan. Objective: To determine the relationship between psychological stress and cortisol levels in patients with breast cancer in Punjab, Pakistan and to measure the effect of demographic and clinical factors on such results. Methods: A cross-sectional design study involving treatment breast cancer patients was done at specific tertiary care hospitals within Punjab Pakistan. There were recruited a total of participants via non-probability convenience method of sampling. The validated standardized questionnaire was used to measure psychological stress, and the cortisol level was measured using biological samples in the laboratory. Data summarization was conducted using descriptive statistics and inferential statistical tests, such as t-tests, ANOVA, and correlation analysis were conducted to assess variable associations. The p value was taken to be below 0.05, which was called statistically significant. Results: The authors discovered that breast cancer patients had high levels of psychological stress scores and cortisol, and the relationship between stress and cortisol levels is significant (p < 0.05). Being younger, unmarried, having lower levels of education, having advanced stage of cancer, and having a positive family history aided significantly in assessing a higher level of stress and cortisol. Cancer stage was also found to be associated with both outcomes (p < 0.001) among clinical variables, which means that the severity of the disease does play a major role in the psychological and physiological stress reactions. Conclusion: The research proved that the level of cortisol in breast cancer patients is closely related to psychological stress, which also indicates the presence of the psychosocial effect on the cancer treatment. It is possible that by incorporating psychological assessment and stress management interventions into the routine oncology care, the well-being of patients can be enhanced and the course of treatment can be affected. Additional longitudinal research would be suggested to investigate causal-relationships and intervention efficacy.